Dilema Pinjaman Online di Indonesia: Tinjauan Sosiologi Hukum dan Hukum Syariah - Arinda Elsa Fitra Elsa (DIKTUM: Jurnal Syariah dan Hukum, 2021)
Technology seems to be very sophisticated at this time, and anyone can gain access to all the human needs that are required, beginning with food, and ending with finance. Many citizens take advantage of this opportunity to start a financial loan industry. Online loans are one of the businesses that can make people easily get money without having to work hard with just enough online based smartphone and easy terms they can get cash immediately. However, because the portion of the claim is not proportional to the amount loaned, this business might indeed render them useless. The aim of the research is to provide an overview of the implementation of online lending and borrowing services, as well as an overview of the positive and negative impacts of online loans. An empirical juridical legal research method was used in this study. The findings of this study are constituted in Article 1 paragraph 3 of the Financial Services Authority Regulation number 77 of 2016, which is a credit and lending protection. It's also desired that this will provide the public with a clear picture of the importance of understanding how to loan and withdraw electronically.